B-Cell Immunophenotyping to Predict Vaccination Outcome in the Immunocompromised - A Systematic Review - Diks, Annieck M.; Overduin, Lisanne A.; van Leenen, Laurens D.; Slobbe, Lennert; Jolink, Hetty; Visser, Leonardus G.; van Dongen, Jacques J. M.; Berkowska, Magdalena A. (Frontiers in Immunology, 2021)
Vaccination is the most effective measure to prevent infections in the general population. Its efficiency strongly depends on the function and composition of the immune system. If the immune system lacks critical components, patients will not be fully protected despite a completed vaccination schedule. Antigen-specific serum immunoglobulin levels are broadly used correlates of protection. These are the products of terminally differentiated B cells – plasma cells. Here we reviewed the literature on how aberrancies in B-cell composition and function influence immune responses to vaccinations. In a search through five major literature databases, 6,537 unique articles published from 2000 and onwards were identified. 75 articles were included along three major research lines: extremities of life (13), immunodeficiency (33) and immunosuppression (29). Details of the protocol can be found in the International Prospective Register of Systematic Reviews (PROSPERO (registration number CRD42021226683). The majority of articles investigated immune responses in adults, in which vaccinations against pneumococci and influenza were strongly represented. Lack of baseline information was the most common reason of exclusion. Irrespective of study group, three parameters measured at baseline seemed to have a predictive value in assessing vaccine efficacy: (1) distribution of B-cell subsets (mostly a reduction in memory B cells), (2) presence of exhausted/activated B cells, or B cells with an aberrant phenotype, and (3) pre-existing immunological memory. In this review we showed how pre-immunization (baseline) knowledge of circulating B cells can be used to predict vaccination efficacy. We hope that this overview will contribute to optimizing vaccination strategies, especially in immunocompromised patients.